Testing the Fair Game Hypothesis for US Dollar/Albanian Lekë Exchange Rate Over the Period January 1994- December 2012 - Sota, Llambrini; Kolaneci, Fejzi (European Journal of Sustainable Development, 2013)
The purpose of the paperis to test the fair game hypothesis for exchange rate process USDollar / Albanian Lekë over theperiod January 1994 – December 2012.The results of this study include: The fairgame hypothesis is rejected for mean monthlyexchange rate US Dollar/Albanian Lekë over the period January 1994 – December 2012at 99.99% level of confidence. Day – to –dayfluctuations of the nominal exchange rateUS Dollar/ Albanian Lekë during the period 1 January 2008 – 31 December 2008 followan unfair game process at99.99% level of confidence.The fair game hypothesis isrejected for mean monthly exchange rateover the period January 2008 – December 2012at 95% level of confidence. Day – to-day fluctuations of nominalexchange rate USDollar/Albanian Lekë during the period1 January 2004 – 31 December 2012 follow anunfair game at 99.99% levelof confidence. A similar result holds for relative firstdifferences of the daily exchange rate USDollar/Albanian Lekëat 99.99% level ofconfidence. These findings are noteworthy because it has long been thought of that themovements in the US dollar / Albanian lekë nominal exchange rate must be a fair game.